(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study calculated the appropriate area of university laboratories which shall allow 40 students to evacuate in the shortest time frame when they evacuate at the walking speed per extinction coefficient of smoke to be created upon outbreak of fire.In the case where the floor area was 600㎡, the required safe egress time (RSET) for the total 40 students was 48.3 seconds when extinction coefficient was 0.3m⁻¹, 52.6 sec when extinction coefficient was 0.5m⁻¹, and 54.3 sec when extinction coefficient was 1.0m⁻¹. In the case where the floor area was reduced to 300㎡, half of the first case, the RSET for the total 40 students was 50.0 sec when extinction coefficient was 0.3m⁻¹, 56.4 sec when extinction coefficient was 0.5m⁻¹, and 54.1 sec when extinction coefficient was 1.0m⁻¹, showing the result that RSET of all the students was rather elongated when extinction coefficient was 0.3m⁻¹ and 0.5m⁻¹ respectively due to bottleneck caused by increase in population density even though the exit distance was shortened. In the case where the floor area was increased to 1200㎡, twice of the first case, RSET of all the levels of extinction coefficient was elongated due to increase in exit distance. As result of the experiments with different size of floor areas, the shortest RSET of all the students was found with 540㎡ of floor area. In conclusion, it was found that the RSET for all the people in the lab shall be shortest when the floor area was appropriate.